Pengaruh kompensasi dan komitmen organisasional terhadap kinerja karyawan serta peran motivasi kerja dalam memediasi pengaruh kompensasi terhadap kinerja karyawan - Adrin , Hetharie Jondry; Abraham , Rieuwpassa (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study was to examine and analyze the effect of compensation, organizational commitment on employee performance and the role of work motivation variables in mediating the effect of compensation relationship on employee performance at PT Midi Utama Indonesia Tbk Ambon branch, Maluku, Indonesia. The sampling technique used is the census technique with a total of 45 respondents who are employees of PT Midi Utama Indonesia Tbk Ambon branch located in the sub-district of Nusaniwe. The analytical test tool used is SmartPLS v.3.2.7 with SEM (Structural EquationModeling) analysis method. The results of this study indicate that compensation has a positive but not significant effect on employee performance, organizational commitment has a positive but not significant effect on organizational commitment, compensation has a positive and significant effect on work motivation, work motivation is proven to mediate the effect of compensation on employee performance.